1991
DOI: 10.1002/ajmg.1320410406
|View full text |Cite
|
Sign up to set email alerts
|

Generalized chondrodysplasia punctata with shortness of humeri and brachymetacarpy: Humero‐metacarpal (HM) type: Variation or heterogeneity?

Abstract: We report on a girl with symmetrical rhizomelic shortness of the upper limbs and punctate epiphyseal calcifications noted at birth. Presumably she has normal height, but short nose, short hands, and normal mentation; and on roentgenograms short and wide humeri, symmetrical brachymetacarpy, especially of the 4th metacarpals, and hypoplastic distal phalanges, sagittal clefting of vertebral bodies, and punctate calcifications at various areas including the entire spine, sacrum, hands, feet, trachea, and thyroid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…We describe a boy with symmetrical upper limb rhizomelic shortness and chondrodysplasia punctata (CDP). Our patient is very similar to that described by Borochowitz [1991] with an apparently new and distinct form of CDP he called chondrodysplasia punctata, humero-metacarpal (CDP-HM) type. We present this case as a second example of the DP-HM type, confirming this as a unique entity.…”
Section: Introductionsupporting
confidence: 86%
“…We describe a boy with symmetrical upper limb rhizomelic shortness and chondrodysplasia punctata (CDP). Our patient is very similar to that described by Borochowitz [1991] with an apparently new and distinct form of CDP he called chondrodysplasia punctata, humero-metacarpal (CDP-HM) type. We present this case as a second example of the DP-HM type, confirming this as a unique entity.…”
Section: Introductionsupporting
confidence: 86%
“…It has been suggested that a rare ‘Humero‐Metacarpal’ form of CDP may represent a distinct entity [Borochowitz, 1991; Fryburg and Kelly, 1996]. Recently a clinical form similar to rhizomelic CDP but without the biochemical features has been described [Kumada et al, 2001].…”
Section: Discussionmentioning
confidence: 99%
“…5 Borochowitz reported an infant with chondrodysplasia punctata and shortened humeri. 6 The infant's mother had type 1 diabetes mellitus and exposure to varicella during the pregnancy. It is unclear if this infant had a variation of the tibial-metacarpal form of chondrodysplasia punctata or an embryopathy acquired in utero that resembles the tibial-metacarpal form.…”
Section: Discussionmentioning
confidence: 99%